Implementasi Pendekatan Objective-Oriented Project Planning dalam Pekerjaan Magang MBKM di PT. Mitra Bangun Kreatifa - Alby Aruna; Henry Praherdhiono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This study aims to implement the Objective-Oriented Project Planning (OOPP) model in the Merdeka Belajar Kampus Merdeka (MBKM) internship program at PT. Mitra Bangun Kreatifa to enhance project performance. The method used is a participatory approach involving internship students in every stage of project planning. These stages include identifying objectives, determining success indicators, and developing and evaluating work plans. The results show that the implementation of the OOPP model significantly improves the efficiency and effectiveness of project execution and provides a more structured and result-oriented learning experience for internship students. Additionally, active participation of students in the project planning process enhances their managerial skills and practical understanding of project management. These findings indicate that the OOPP model can be an effective framework for internship programs focused on improving project performance and developing student competencies.